Intraocular lens bicylindric power calculation method: Using both flat and steep K readings to improve intraocular lens power prediction. Issue 5 (September 2018) - Calvo-Sanz, Jorge A; Ruiz-Alcocer, Javier; Sánchez-Tena, Miguel A
Purpose: To compare and analyze the accuracy of the refractive outcomes obtained in intraocular lens power calculation using the classical calculation method with mean keratometry (K) and the calculation method with both K meridians presented in this article. Methods: A total of 62 eyes of 62 subjects who were undergoing cataract surgery were included in this study. Optical biometry was performed using mean K and Haigis formula for classical intraocular lens calculation methods to achieve intraocular lens power; 4 weeks after surgery, prior to medical discharge, subjective refraction was made. Alternatively, intraocular lens power was calculated with bicylindric method using both keratometry readings, obtaining spherocylindrical refractive expected outcomes. Finally, results obtained with intraocular lens calculation methods, bicylindric method, and Haigis formula were compared. Results: Spherical equivalent calculated by classical intraocular lens calculation methods using Haigis formula (H-SE) was −0.027 ± 0.115 D and using bicylindric method (B-SE) was −0.080 ± 0.222 D. Achieved spherical equivalent obtained 4 weeks after surgery (A-SE) was −0.144 ± 0.268 D. Difference between H-SE and A-SE was −0.117 D (p = 0.002). Difference between B-SE and A-SE was not significant (−0.054 D, p = 0.109). Analysis in refraction groups showed a positive correlation between A-SE confronted to B-SE and H-SE (r = 0.313; p = 0.013 and r = 0.562; p < 0.001, respectively). This indicated a reliability in ametropic group prediction of 0.767 in H-SE and 0.843 in B-SE. Conclusion: Intraocular lens calculation with bicylindric method could be more accurate and had more reliability than classical intraocular lens calculation method. Bicylindric method adds astigmatism control and provides a reliable expected spherocylindrical refraction.